Penggunaan Artificial Intelligence (AI) dalam Pembelajaran: Fenomena Transformasi Otoritas Pengetahuan di Kalangan Mahasiswa - Fera Andriani Djakfar Musthafa (Journal of Contemporary Islamic Education, 2024)
Currently, the use of artificial intelligence has become widespread, especially among students. However, there is a consensus that artificial intelligence brings about some changes in students' intellectual lives, particularly when used excessively. One of the tangible transformations is related to the authorithy of knowledge, where students prefer to complete assignments with the assistance of artificial intelligence without seeking other authoritative sources. This research aims to find answers to the following questions: How has the use of artificial intelligence spread among students? What significant changes in students' intellectual lives as the impact of excessive use of artificial intelligence, particularly concerning the transformation in the authority of knowledge? This study is a qualitative research with a phenomenological approach to investigate a variety of phenomena surrounding the research topic directly from the field. The research was conducted in the Department of Arabic Language Education at STAI Syaichona Moh. Cholil Bangkalan. This research found that: students use AI in learning, such as ChatGPT, chatbots, and AI-based electronic dictionaries, primarily because their lectures are related to language translation. Furthermore, this research also found that a transformation in the authority of knowledge has occurred, transitioning from lecturers and authoritative books to reliable websites, opinions of intellectual figures, and journals published by universities.